Legal Treatment Standards for International Investments. Heuristic Aspects. - Tache, Cristina-Elena Popa. (Adjuris - International Academic Publishers, 2021)
Discussing the standards of legal treatment for international investment, means subjecting the law branch in its entirety to research. Representing the most comprehensive part, of particular importance for international investment law, treatment standards continue to generate a series of differentiations whose understanding and approach often require the analysis of the starting points that led to the emergence, by division, of this branch of law. International investment treatment standards represent or should represent the direct effect of the principles of international investment law, thus being their expression, with a pronounced logical affinity between them.